Center store. - United States. Army. Signal Corps (photographer):::Creator::::::::::::; Flaherty, John Melvin (collector):::Contributor::::::::::::
Photograph shows one of the Pomona, California Assembly Center stores displaying various sections of goods available for purchase with evacuees buying goods.